TASAWUF SEBAGAI METODE UNTUK MENINGKATKAN AKHLAH, MENGUATKAN JIWA dan MENDEKATKAN DIRI KEPADA ALLAH SWT - Eliyah Eliyah (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2020)
Sufism characters include: a) Increasing morals; b) Having the spiritual experience of immersing oneself in the Supreme Being; c) Knowledge of God is direct; d) Peace and spiritual happiness; and e) Symbolic disclosure of teachings; The goals of Sufism include: a) Ma'rifat billah, is to see God with their hearts clearly and clearly with all its enjoyment and greatness; b) Individual Kamil, who has achieved the dignity and degree of perfection; and the characteristics of Sufism are to: a) Increase morals (At-Taraqqi al-Akhlaqi); b) Spiritual experience of immersion in the Supreme Essence (Al-Fana 'fi Haqiqat Al-Asma'); c) Knowledge of God is direct (Al-Irfan Al-Dzawqi Al-Mubasyir); d) Peace and spiritual happiness (Ath-Thumaninahwa As-Sa'adah Ar-Ruhiyyah; and e) Symbolic expression of teachings (Ar-Rumziyyah fi At-Ta'bir).